2020
DOI: 10.1177/0963689720933241
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-based Diagnostic and Prognostic Biomarkers for Glioblastoma

Abstract: Glioblastomas are the most common primary central nervous system malignancy tumor in adults. Glioblastoma patients have poor prognosis, with an average survival period of approximately 14 mo after diagnosis. To date, there are a limited number of effective treatment methods for glioblastoma, and its molecular mechanisms remain elusive. In this article, we analyzed the key biomarkers and pathways in glioblastoma patients based on gene expression and DNA methylation datasets. The 60 hypomethylated/upregulated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…5 Calcium signaling pathway, ECM-receptor interaction, and c-AMP signaling pathway were found to be the significant differences between the patients with IDH1 and TP53 mutations and the patients with wild-type, which played important cooperating roles in the glioma tumorigenesis. 30,31 Interestingly, nicotine addiction and morphine addiction were also found to be a significant difference between the patients with IDH1 and TP53 mutations and the patients with wild-type, which was also reported in the previous GBM studies, [32][33][34] but here suggested could be closely related to the IDH1 and TP53 mutations. In the LGG cohort, the patients with IDH1 and TP53 mutations seem to have many immunological changes than the patients with wild-type, for example, the anti-viral function (defense response to virus, negative regulation of viral process, and type I interferon signaling pathway), which might indicate that the immune status in the patients with IDH1 and TP53 mutations is different from the patients with wild-type.…”
Section: Discussionsupporting
confidence: 88%
“…5 Calcium signaling pathway, ECM-receptor interaction, and c-AMP signaling pathway were found to be the significant differences between the patients with IDH1 and TP53 mutations and the patients with wild-type, which played important cooperating roles in the glioma tumorigenesis. 30,31 Interestingly, nicotine addiction and morphine addiction were also found to be a significant difference between the patients with IDH1 and TP53 mutations and the patients with wild-type, which was also reported in the previous GBM studies, [32][33][34] but here suggested could be closely related to the IDH1 and TP53 mutations. In the LGG cohort, the patients with IDH1 and TP53 mutations seem to have many immunological changes than the patients with wild-type, for example, the anti-viral function (defense response to virus, negative regulation of viral process, and type I interferon signaling pathway), which might indicate that the immune status in the patients with IDH1 and TP53 mutations is different from the patients with wild-type.…”
Section: Discussionsupporting
confidence: 88%
“…Methylation-based subtypes that predict GBM patient survival have been reported. Notably, the methylation levels of different subgroups could reflect different molecular genetic features 22 , 23 . More and more attention has been paid to the relationship between the immune system and malignancy progression and pathogenesis, which contribute to GBM treatment, thereby promoting the development of anti-tumor treatments.…”
Section: Discussionmentioning
confidence: 99%
“…7). The PI3K/Akt signaling pathway regulate DNMT3B protein expression level, thus regulating the chemosensitivity of glioblastoma cells to TMZ It's well known that DNA methylation is a crucial regulator in tumor development [10]. And previous study had demonstrated the PI3K/AKT pathway regulates the expression of DNMT3B in some tumor [21].…”
Section: Differentially Expressed Genesmentioning
confidence: 98%
“…Epigenetic modi cation, a biological process that modi es gene regulation without altering DNA sequence [12,13], is well-established as a key factor in tumor-related gene expression, including chromatin remodeling, histone modi cation, and DNA methylation. [10]. DNA methylation, occurring at the 5th position of Cytosines at CpG site, is catalyzed by DNA methyltransferases (DNMTs) [14,15].…”
Section: Introductionmentioning
confidence: 99%